Epidemiology and demographics of aggressive periodontitis. (June 2014) - Susin, Cristiano; Haas, Alex N.; Albandar, Jasim M.
Abstract: Epidemiologic studies of aggressive periodontitis have used different study designs and a range of examination methods and case definitions, and this greatly complicates the study of disease prevalence in populations. The wide range of disease case definitions, in particular, profoundly impacts the reported rate of disease, and the use of a standard disease definition is strongly recommended. Surveys of aggressive periodontitis that use only clinical examinations, without radiographic examination to confirm the presence of a distinctive pattern of tissue loss, may overestimate the prevalence of this disease, particularly when a low threshold of attachment loss is used. The prevalence of aggressive periodontitis varies significantly between populations, and differences in race/ethnicities seem to be a key factor. Studies consistently show that aggressive periodontitis is most prevalent in Africa and in populations of African descent and is least prevalent in Caucasians in Europe and North America. Among children and young adults the prevalence of this disease is higher in older than in younger age groups. Most studies show comparable disease prevalence in male and female subjects. These findings show that aggressive periodontitis is a significant health problem in certain populations. This review also highlights a lack of information on the epidemiology and demographics of this disease in many parts of the world, particularly in Asia and Africa. Epidemiologic studies of aggressive periodontitis in high‐risk populations are important and could provide vital data on the determinants of this disease, and this information is needed for the establishment of effective health‐promotion measures.